MAKNA VERBAL DAN NONVERBAL DALAM TARIAN LALA KAJIAN ANTROPOLINGUISTIK - Justam Wahab; Darlisa Muhammad (Universitas Khairun, 2023)
Research purposes knowing how verbal and non-verbal meanings in the anthropolinguistic study lala dance! To what extent are the verbal and non-verbal meanings in the anthropolingusistic lala dance? Research Methods Research Methodology Researchers used a qualitative descriptive method. Qualitative research is a study aimed at describing and analyzing phenomena, events, social activities, attitudes, beliefs, perceptions, thoughts, people individually or in groups. The results of the observations that the researchers obtained while conducting the research started from January 3, 2023 to February 5, 2023. Based on the results of observations made by researchers in the research process in Sagea Village, North Weda District, Central Halmahera Regency, the Lala traditional dance movement was taken from the story of a woman which mimics the movements of seagulls when they are preparing to jump to catch fish.